Analysis of The Influence of Work Discipline And Employee Motivation on Employee Performance BMT Beringharjo - Rahma Yudi Astuti; Muhammad Wafiyuddin Balya Mahdi (Islamic Business and Management Journal, 2023)
Human resources (HR) will play a positive or negative role in the performance of a company by applying work discipline and work motivation. However, BMT Beringharjo Still long work motivations based on Islamic values to improve HR performance. In addition, the success of the company is largely determined by the style of work motivation that exists in the organization that will affect employee performance. BMT Beringharjo is an Islamic-based which implements in accordance with the company's VISION, namely "Leading bras trusted Sharia-Based business partner" in its company so as to improve employee performance. Therefore, this study will analyze how far the influence of work discipline in the organization and the work motivation retrered on improving the performance of BMT Beringharjo. This research uses a quantitative approach. The data collection technique used is primary data, by spreading questionnaires. Data was obtained from the employee population of 31 people. Data analysis using SPSS 26 which was analyzed deductively. The results of this study show that work discipline has a positive effect on employee performance with a sig of 0.002< 0.1, while Islamic work motivation has a positive effect on employee performance at BMT Beringharjo with a sig of 0.034< 0.1. With This result, the influence of work discipline and work motivation in it can get closer to Allah SWT through the practice carried out in every work in it. Recommendations for the company itself to always improve work discipline and work motivation in order to create an Islamic organizational culture in accordance with the existing vision, namely " Leading Bras, Trusted sharia Based business Sharia